Solar-energy camouflage coating with varying sheet resistance. (November 2020) - Dong, Fu-Yan; Xu, Su; Guo, Wenrui; Jiang, Nai-Rong; Han, Dong-Dong; He, Xing-Yi; Zhang, Liu; Wang, Zuo-Jia; Feng, Jing; Su, Wenming; Sun, Hong-Bo
Abstract: Solar-energy camouflage coating that avoids being detected by radars and simultaneously preserves solar-energy power conversion efficiency (PCE) is of great importance for hiding facilities (e.g. satellites) with solar-energy systems. However, widely used multilayer architecture of uniform sheet resistance (US) for broadband camouflage will sacrifice the transparency and extremely deviate the PCE-preservation requirement of solar-energy systems. Here, we propose an architecture of varying sheet resistance (VS) for solar-energy camouflage, by which the aforementioned technical deviation can be solved. By imprinting metallic nanowire-based circuits, a VS-based solar-energy camouflage coating with an 88% transparency and 2.7-mm thickness is demonstrated experimentally as a proof of concept. When the camouflage is achieved from 7.2 to 18.5 GHz, our sample can realize a 95% (92%) PCE preservation for a perovskite (silicon) solar cell, and such a high value is not reported before. Compared to US-based works, the comprehensive performance of our VS-based sample can be improved by 8.3%, which is the highest record ever to the best of our knowledge. Our work extends the concept of structural nano-circuit from US architecture to VS architecture and paves the way towards the practical invisible satellites as well as advanced solar-energy devices. Graphical abstract: Image 1 Highlights: The architecture of varying sheet resistance has been proposed for the camouflage of solar-energy system. Nonuniform metallic nanowires ensure the simultaneous realization of power-conversion-efficiency preservation and camouflage. The power conversion efficiency of a perovskite (Silicon) solar cell is preserved at the levels of 95% (92%). The comprehensive performance of our solar-energy camouflage coating is the highest record ever.